Formulation, Characterization and Optimization of Mouth Dissolving Tablets of Diacerein: Β-Cyclodextrin Solid Dispersion - Gupta, Khem chand; Singhvi, Indrajeet (Asian Journal of Pharmaceutical Research and Development, 2015)
Diacerein is a poorly water soluble drug and bioavailability from its crystalline form is very low. The purpose of the present investigation was to increase the solubility and dissolution rate of Diacerein by preparing a solid dispersion with β- cyclodextrin (β-CD) using Kneading method. The dissolution profiles of developed formulations in acetate buffer pH 4.5 containing 0.45% SLS were studied. The prepared complexes were characterized by Fourier transform infra red spectroscopy (FTIR), differential scanning calorimetry (DSC) and powder X-ray diffractometry (PXRD). For the preparation of Diacerein mouth dissolving tablets, a 1:2 (Diacerein: β-CD, Batch DK3) solid dispersion was used with LHPC and croscarmellose sodium as a superdisintegrant. A 32 full-factorial design was employed to study the effect of independent variables, the amounts of L-HPC (X1) and croscarmellose sodium (X2) on dependent variables disintegration time and percentage friability. FTIR, DSC and PXRD data indicate that Diacerein was in the amorphous form, which explains the faster dissolution rate of the drug from its solid dispersions. Concerning the optimization study, multiple regression analysis reveals that an optimum concentration of croscarmellose sodium and a higher percentage of L-HPC are required for obtaining rapidly mouth dissolving tablets. Accelerated stability studies of mouth dissolving tablets carried out as per ICH guidelines revealed that the tablets were stable